2013
DOI: 10.5801/ncn.v16i1.896
|View full text |Cite
|
Sign up to set email alerts
|

Um olhar sobre os Colegiados dos Territórios da Cidadania no Pará.

Abstract: ResumoNo Brasil, as políticas territoriais e, em particular, os Territórios da Cidadania, representam inovações institucionais interessantes. A avaliação e o melhoramento delas necessitamde uma análise dos mecanismos diferenciados da ação pública, e suas consequências concretas sobre as formas de territórios resultantes. A partir do exemplo do estado do Pará, a relação entre a diversidade de dinâmicas territoriais e o funcionamento diferenciado dos colegiados dos Territórios da Cidadania é analisada, a partir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
1
2
0
4
Order By: Relevance
“…From our initial interviews, we found that only a small number of people had participated on an ongoing basis in the meetings of the territorial arrangements. This finding is in line with studies carried out at the level of the country (Delgado and Grisa ) or of the state of Pará (Piraux et al ), which reveal a high turnover of participants. They have prompted us to focus on the actors who are genuinely involved in the arrangements, that is to say, whose participation was significant and whose reasoning could have been influenced by the implementation of those arrangements.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…From our initial interviews, we found that only a small number of people had participated on an ongoing basis in the meetings of the territorial arrangements. This finding is in line with studies carried out at the level of the country (Delgado and Grisa ) or of the state of Pará (Piraux et al ), which reveal a high turnover of participants. They have prompted us to focus on the actors who are genuinely involved in the arrangements, that is to say, whose participation was significant and whose reasoning could have been influenced by the implementation of those arrangements.…”
Section: Methodssupporting
confidence: 91%
“…We have examined the implementation of the programme ‘Territories of Citizenship’ in the Pará state (Figure ), which has achieved some success in terms of participation and of the actions implemented (Piraux et al ), despite the low population density of the state, the weakness of its institutions and the environmental challenges they face. In this state, the emancipation of civil society materialized in the takeover of agricultural unions (formerly in the hands of local leaders) by the rural workers, then expressing social demands.…”
Section: Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…O insuficiente nível de acumulação de capital humano, o despreparo e o baixo grau de apropriação do instrumento (PIRAUX et al, 2013;FREITAS et al, 2012), a forma de implantação da política, não acompanhada pela devida contextualização e focada na alocação de recursos (FREITAS et al, 2012), a falta de definições metodológicas sobre a condução do processo de implantação e condução dos Colegiados (FAVARETO et al, 2010;CAZELLA;BÚRIGO, 2008), e a setorialidade em suas composições (FAVARETO et al, 2010;CAZELLA;BÚRIGO, 2008) acompanhados por processos de "partidarização" de suas gestões (CAZELLA;BÚRIGO, 2008;PIRAUX et al, 2013), parecem ter levado a um curto-circuito em seu funcionamento.…”
Section: O Codeter Do Baixo Tocantins Compreendido Como Arena Socialunclassified
“…De um modo geral, o PROINF nos Territórios, além de problemas na contratação, também teve problemas na execução, como no Território Açu/Mossoró, no Rio Grande do Norte, onde a maioria dos projetos, não estava funcionando, conforme relatório de pesquisa da Célula desse Território realizada entre os anos de 2010 e 2011 (Nunes et al, 2015). Piraux et al (2013), tratando dos Territórios da Cidadania no Pará, destaca que dos 65 projetos aprovados, somente 33 estavam como normais ou concluídos. No Piauí, Lima (2010) apresenta problemas semelhantes nos projetos do PROINF do Território dos Carnaubais.…”
Section: Considerações Finaisunclassified